2019
DOI: 10.3390/ma12060860
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Machining Strategy Selection in Ball-End Milling of Hardened Steels for Injection Molds

Abstract: In the present study, the groups of cutting conditions that minimize surface roughness and its variability are determined, in ball-end milling operations. Design of experiments is used to define experimental tests performed. Semi-cylindrical specimens are employed in order to study surfaces with different slopes. Roughness was measured at different slopes, corresponding to inclination angles of 15°, 45°, 75°, 90°, 105°, 135° and 165° for both climb and conventional milling. By means of regression analysis, sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The surface finish of cams is important, because low roughness reduces friction in the cam-roller contact [27]. Roughness has been measured with a contact profile meter, as is usual in metallic parts with curved surfaces [44]. Shape error is important since better accuracy of the cam profile will favor the compliance with the motion-law of the follower and, consequently, better operation of the mechanism [2].…”
Section: Discussionmentioning
confidence: 99%
“…The surface finish of cams is important, because low roughness reduces friction in the cam-roller contact [27]. Roughness has been measured with a contact profile meter, as is usual in metallic parts with curved surfaces [44]. Shape error is important since better accuracy of the cam profile will favor the compliance with the motion-law of the follower and, consequently, better operation of the mechanism [2].…”
Section: Discussionmentioning
confidence: 99%
“…The validation of the proposed models, conducted on the basis of the ANOVA method, proves their applicability to the optimization of aluminum matrix composite manufacturing during the fused deposition modeling assisted by the investment casting. Buj-Corral et al [9] employed a central composite design to model the behavior of surface roughness during ball end milling of hot work-hardened tool steel W-Nr, consisting of a two level factorial design with four factors (24 = 16 experiments), and four central points. The conducted studies have shown that the radial depth of the cut was the most relevant factor on Ra and Rt for both climb and conventional milling.…”
Section: Ofmentioning
confidence: 99%
“…Zhou et al [23] developed a modified grey relational analysis model for optimizing the surface roughness and residual stress in the ball-end milling of Inconel 718. Buj-Corral et al [24] developed an artificial neural network for correlating surface roughness with cutting parameters to obtain the optimal machining strategy in the five-axis ball-end milling of W-Nr. 12344.…”
Section: Introductionmentioning
confidence: 99%